African developments: competing institutional arrangements for climate policy: the case of Nigeria - Peter Koblowsky; Chinwe Ifejika Speranza (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
This policy brief analyses national-level multi-stakeholder processes relating to climate change, taking the case of Nigeria as its example, and draws some inferences on how to make progress in the areas of climate change governance and institutional change in the context of competing proposals for institutional arrangements in the climate policy process. Nigeria illustrates the complex case of multiple stakeholders in a developing and oil-exporting country that is both emitting greenhouse gases and highly vulnerable to climate change impacts. The climate policy process in Nigeria is quite a novelty for the country: rarely has such a wide group of stakeholders from the key sectors of society together elaborated a wide-ranging policy. The actors include the Federal Ministry of Environment; the parliament and the Presidency; the Nigerian National Petroleum Corporation; the private sector; civil society networks and nongovernmental organisations (NGOs); donors and international organisations. While Nigeria's Federal Ministry of Environment (FMEnv) has hitherto been responsible for Nigeria's climate change responses at national and international level, there is a generally recognised need to improve the governance of climate change in Nigeria. Policy processes involving various stakeholders pursuing this common goal have resulted in two competing proposals for new institutional arrangements: the creation of (A) a National Climate Change Commission reporting directly to the presidency and (B) a National Agency directly affiliated to the FMEnv. Although the parliament adopted the Commission Bill, the Nigerian President had still to sign it one and a half years later, and it was sent back to the National Assembly. The outcomes thus remain uncertain. This disagreement reveals a lack of trust and a struggle for political influence among stakeholders who were apparently working towards the same goal of improving climate governance and strengthening inter-ministerial coordination. Two key messages can be highlighted: The proposed institutional arrangement involving the creation of a National Climate Change Commission could be expected to improve coordination at national level between the federal ministries, business and civil society and to ensure linkages with the six geo-political zones of Nigeria, and the Commission would therefore wield more political influence than the FMEnv. Consequently, it seems that the Commission would serve the useful purpose of improving the governance of climate change in Nigeria. However, it would strip the FMEnv of most of its powers. It would therefore be advisable to give the FMEnv a more prominent role in the Commission'sactivities. The latter could then tap into the institutional memories and competences accumulated by the FMEnv over 20 years. A division of roles between the Commission and the FMEnv and an accurate definition of their respective responsibilities would thus be a critical target baseline.
Keywords: 330; Governance; Klimawandel